Large Methane Emissions From the Pantanal During Rising Water‐Levels Revealed by Regularly Measured Lower Troposphere CH4 Profiles. Issue 10 (10th October 2021) - Gloor, M.; Gatti, L. V.; Wilson, C.; Parker, R. J.; Boesch, H.; Popa, E.; Chipperfield, M. P.; Poulter, B.; Zhang, Z.; Basso, L.; Miller, J.; McNorton, J.; et al.
Abstract: The Pantanal region of Brazil is the largest seasonally flooded tropical grassland and, according to local chamber measurements, a substantial CH4 source. CH4 emissions from wetlands have recently become of heightened interest because global atmospheric 13 CH4 data indicate they may contribute to the resumption of atmospheric CH4 growth since 2007. We have regularly measured vertical atmospheric profiles for 2 years in the center of the Pantanal with the objectives to obtain an estimate of CH4 emissions using an atmospheric approach, and provide information about flux seasonality and its relation to controlling factors. Boundary layer‐free troposphere differences observed in the Pantanal are large compared to other wetlands. Total emissions based on a planetary boundary layer budgeting technique are 2.0–2.8 TgCH4  yr −1 (maximum flux ∼0.4 gCH4  m −2  d −1 ) while those based on a Bayesian inversion using an atmospheric transport model are ∼3.3 TgCH4  yr −1 . Compared to recent estimates for Amazonia (∼41 ± 3 TgCH4  yr −1, maximum flux ∼0.3 gCH4 m −2  d −1 ) these emissions are not that large. Our Pantanal data suggest a clear flux seasonality with CH4 being released in large amounts just after water levels begin to rise again after minimum levels have been reached. CH4 emissions decline substantially once the maximum water level has been reached. While predictions with prognostic wetland CH4 emission models agree well with the magnitude of the fluxes, they disagree with the phasing. Our approach shows promise for detecting and understanding longer‐term trends in CH4 emissions and the potential for future wetlands CH4 emissions climate feedbacks. Plain Language Summary: CH4 emissions contribute substantially to greenhouse warming and atmospheric concentrations continue to grow rapidly. Increases in emissions from wetlands may contribute. We have measured regularly vertical CH4 concentration profiles over the Pantanal, the largest tropical seasonally flooded grasslands, to provide an estimate of these emissions and to determine seasonal cycle. Our estimates are similar to earlier estimates based on direct flux measurements on the ground. Fluxes vary strongly seasonally. They are largest during the rise of water levels and decrease before maximum levels have been reached. Our data show that longer‐term vertical profile measurements could provide an answer whether wetland emissions are changing. Key Points: Large CH4 boundary layer‐free troposphere differences over Pantanal wetlands revealed by vertical atmospheric CH4 profile data According to atmospheric data, CH4 flux is large during the early expansion phase of the inundated area and weakens at peak extent Prognostic global wetlands CH4 emission models have limited skill regarding seasonality of Pantanal emissions